Fas-Related Apoptosis of Peritoneal Fluid Macrophages in Endometriosis Patients: Understanding the Disease. (1st November 2017) - Gogacz, Marek; Gałczyński, Krzysztof; Wojtaś, Małgorzata; Winkler, Izabela; Adamiak, Aneta; Romanek-Piva, Katarzyna; Rechberger, Tomasz; Kotarski, Jan
Abstract : Recent studies of the peritoneal cavity environment in endometriosis demonstrate quantitative and qualitative changes in the cells responsible for cell-mediated immunity. Such changes may have led to disturbances in the surveillance, recognition, and destruction of misplaced endometrial cells and might have, in fact, brought about the disease. The aim of the study was to assess CD95 (Fas) expression on (activated) peritoneal fluid (PF) macrophages, as well as to ascertain soluble Fas (sFas) concentration in the PF of endometriosis patients, as compared to the nonendometriotic group. The concentration of leukocytes in the PF, the percentage of cells expressing CD45 + /CD14 +, and the percentage of PF macrophages expressing the HLA-DR antigen were significantly higher in patients with stages I and II endometriosis. The percentage of Fas- (CD95 + -) expressing macrophages was significantly higher in all stages of the disease, in comparison with controls. Moreover, the concentration of sFas in the PF of patients with moderate and severe endometriosis was significantly higher, as compared to the reference group. The high number of immune cells in PF in early stage endometriosis and their increased susceptibility to apoptosis confirm the role of the impaired peritoneal environment and immune defects in the development and progression of the disease.